2023
DOI: 10.3389/fped.2023.1043067
|View full text |Cite
|
Sign up to set email alerts
|

Predicting complications in pediatric Crohn's disease patients followed in CEDATA-GPGE registry

Abstract: BackgroundComplications of Crohn's disease (CD) often impair patients' quality of life. It is necessary to predict and prevent these complications (surgery, stricturing [B2]/penetrating [B3] disease behavior, perianal disease, growth retardation and hospitalization). Our study investigated previously suggested and additional predictors by analyzing data of the CEDATA-GPGE registry.MethodsPediatric patients (< 18 years) diagnosed with CD with follow up data in the registry were included in the study. Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Daher bedarf es einer individuellen Begleitung. Ein kleineres Kind hat andere Ängste und Bedürfnisse als ein pubertierender Teenager, der Probleme hat, die Erkrankung zu akzeptieren mit all ihren Einschränkungen: „Jugendliche weisen gemäß verschiedenen Studien eine schlechtere Adhärenz auf als jüngere Kinder“ 1 2 . Auch können laut Dr. med.…”
Section: Adhärenz Im Jugendalterunclassified
“…Daher bedarf es einer individuellen Begleitung. Ein kleineres Kind hat andere Ängste und Bedürfnisse als ein pubertierender Teenager, der Probleme hat, die Erkrankung zu akzeptieren mit all ihren Einschränkungen: „Jugendliche weisen gemäß verschiedenen Studien eine schlechtere Adhärenz auf als jüngere Kinder“ 1 2 . Auch können laut Dr. med.…”
Section: Adhärenz Im Jugendalterunclassified
“…Therefore, several clinical disease activity indices (DAIs) were developed using noninvasive clinical and standard laboratory parameters for monitoring the severity of CD-associated intestinal inflammation in clinical practice. For example, the Pediatric Crohn's Disease Activity Index (PCDAI) ( 4) is determined regularly in the CEDATA-GPGE registry including data of 6,233 pediatric patients with inflammatory bowel disease (IBD) in 2022 (5). However, the PCDAI, developed in 1991, has not been validated against established endoscopic disease activity scores and includes subjective variables which may potentially compromise its predictive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have attempted to pinpoint prognostic factors of disease course in both children and adults, in real-life practice each patient's disease course remains somewhat unpredictable. [6][7][8] This can make it challenging to decide on a tailored treatment strategy early at the diagnosis. In 2021, Wintjens et al 9 reported data from a cohort of 432 adult patients with CD, divided into 6 clusters of activity in a 10-year follow-up.…”
Section: Introductionmentioning
confidence: 99%